Effect of a lime-based bedding conditioner on physical-chemical characteristics and microbiological counts of recycled manure solids - Freu, Gustavo; Fusar Poli, Sara; Monistero, Valentina; Biscarini, Filippo; Rota, Nicola; Hossain, Delower; Gusmara, Claudia; Musa, Laura; Gioia, Gloria; Leso, Lorenzo; Veiga dos Santos, Marcos; Moroni, Paolo; et al. (Frontiers in Veterinary Science, 2024)
Bedding materials are aimed at providing a safe and comfortable resting environment for cows. Control of pathogen proliferation in these substrates is crucial to prevent intramammary infections in dairy cows, as these can significantly impact milk quality, cow health, and farm productivity. This is particularly relevant in the case of organic bedding substrates, including manure-derived materials. This study aimed to evaluate the in vitro effect of a lime-based conditioner (LBC), composed of CaCO3MgCO3 and Ca(OH)2*Mg(OH)2, at increasing concentrations on the physical-chemical characteristics and bacterial counts of untreated anaerobically digested manure solids (ADMS) and separated raw manure solids (SRMS). Unused ADMS and SRMS were evaluated at four LBC weight-based concentrations: 0 (as untreated control), 10, 15, and 20% of LBC inclusion. The bedding materials were assessed immediately after LBC addition (0 h) and after 24, 72, and 168 h of storage at 28°C. The dry matter content (DM), and pH were measured for all the time points. Standard microbiological methods were used to assess total bacterial counts (TBC), other Gram-negative bacteria, coliforms, Escherichia coli, and streptococci and streptococci-like organism (SSLO). It was observed a linear increase in both DM and pH with increasing concentrations of LBC. Specifically, for each percentage unit increase of LBC, the DM of ADMS and SRMS increased by 0.73 and 0.71%, respectively. Similarly, for each percentage unit of LBC, the pH of ADMS and SRMS increased by 0.15 and 0.19, respectively. Conversely, a linear decrease in TBC, Gram-negative bacteria, coliforms, E. coli, and SSLO was observed with increasing concentrations of the LBC. Manure-derived materials without the inclusion of the LBC had bacterial counts that tended to remain high or increase over time. Otherwise, bedding materials with LBC application had reduced bacterial counts. Based on the results of the present study, it was observed that the higher the concentration of LBC, the more significant the reduction of bacterial counts. Specifically, bacterial recovery was lower when higher concentrations of LBC were applied. Our findings underscore the potential of LBC in effectively controlling environmental bacteria and improving the physical-chemical characteristics of manure-derived bedding materials to improve cow health and welfare.